The exceptional role of the Baghdad Rescue Police in the foreign wars of Iraq 1980-1991 (Journal of the College of Basic Education, 2023)
The Baghdad Rescue Police had an exceptional role in the wars that Iraq entered in the years 1980-1991, whether with Iran or with the United States of America and the international coalition that participated with it. These wars cast a dark shadow over Iraqi society in these years, and the Baghdad Rescue Police assumed double tasks to preserve the internal situation in Iraq, secure social peace, and prevent the deterioration of the security situation in the Iraqi capital